Principal's Strategy in Developing Religious Character in Elementary Education Institution: Strategi Kepala Sekolah dalam Meningkatan Karakter Religius di Lembaga Pendidikan Dasar - Nurjani, Nurjani; Assyairi, Muhammad Yazid; Husna, Nurul; Mubaraq, Muhammad Zaki (Universitas Muhammadiyah Sidoarjo, 2025)
The problem of student character degradation is an urgency in this day and age because there are many phenomena of student behavior now that lack of polite and moral manners. This can cause a decrease in religious character values that are embedded in religious norms. This study focuses on exploring the strategies used by the principal of SDN Panangian in improving religious character in students by implementing religious programs carried out as a step to improve students' religious character in elementary education institution. The research method used is a qualitative design with a case study approach. Data were collected through in-depth interviews with the principal and 8 teachers involved, observation of activities, and analysis of related documents. The results showed that elementary school adopt various strategies in improving students' religious character through religious programs such as; (1) Tahsin, (2) Tahfidz, (3) Dhuha Prayers in Congregation, (4) Dzuhur Prayers in Congregation, (5) Reading Surah Yasin, Al Waqiah and Al Mulk, (6) Tadaruss Al Qur'an, (7) Reciting of Short Surahs (Juz Amma) Every Morning. The strategy of implementing this religious program also collaborates with the STIQ college (College of Qur'anic Studies) as an accelerated step in improving students character and this strategy has provided results in improving students' religious character such as Taqwa, Politeness, Honesty, Responsibility and Discipline, accustomed to daily worship activities at school and creating an environment of elementary educational institution with Islamic character.